Neanderthal adaptive introgression shaped LCT enhancer region diversity without linking to lactase persistence in East Asian populations - Xixian Ma; Yan Lu; Mark Stoneking; Shuhua Xu (Proceedings of the National Academy of Sciences, 2025)
Positive selection at the 2q21.3 enhancer region for lactase gene ( LCT ) expression in Europeans and Africans has long been attributed to selection for lactase persistence (LP), the capacity of adults to digest lactose in milk, presumably because of the benefits associated with milk consumption. While considered a classic example of gene–culture coevolution, recently doubts have been raised about the link between selection at 2q21.3 and LP. Analysis of additional populations could shed further light; here, we demonstrate that a haplotype spanning ~467 kb at the 2q21.3 locus has risen to high frequency in East Asians (~25%) but is absent from Africans and Europeans. This haplotype likely derived from Neanderthals and has been under positive selection in East Asians. The East Asian–specific haplotype is associated with alterations in LCT expression and promoter methylation in certain cell types, similar to what is observed with LP-associated haplotypes in Europeans. Moreover, its frequency is comparable to that of LP in East Asians, suggesting a potential association with LP in East Asians. However, it is highly unlikely that selection in East Asians was related to milk-drinking habits. We find that this haplotype impacts the expression of UBXN4 , DARS1, and DARS1-AS1 in immune cells and is associated with neutrophil and white blood cell counts. Hence, the selection might be linked to certain aspects of immune function. This implies that selection on 2q21.3 has thus either occurred for different reasons in different populations or the selection observed in other populations is also not due to LP.